(untitled) (Baghdad Science Journal, 2015)
The aims of study were identify the Morphological description and histological structure of pancreas gland in the Saw-scaled viper snake, (Echis carinatus scochureki). The study was conducted on 6 snakes collected from the city of Nasiriya in Dhi Qar province, Doped snakes was dissected to isolate the pancreas gland, and the histological slides prepared after samples fixation by fixative solutions, the routine stains Haematoxylin– Eosin were used. Morphological Description study showed that the pancreas gland was compact in type with one lobe, white-pink in colure. The pancreas Located at the level of the Gall bladder associated with it’s caudal side, The spleen is adjacent to pancreas completely in the dorsal side .and duodenum linked to pancreas in the ventral side. The pancreas is mixed gland (endocrine and exocrine) surrounded by a capsule which extends trabeculae with blood vessels inside the gland. The exocrine part represent by the acini which were consisted of pyramidal cells with basal spherical nuclei, attached with each other forming a lumen in the center of the acinus penetrated by centro-acinar cells (flat epithelial cells) Opening in intercalated duct which lined by simple squamous epithelial Tissue, leading to intralobular duct then to interlobular ducts, both lined by simple cuboidal epithelial tissue these ducts leading to the main pancreatic duct which Lined by Ciliated columnar epithelium, as well as, interlobular and Main ducts surrounded by dense connective tissue, While The endocrine part of the pancreas is represented by islets of Langerhans Scattered in the peripheral part of the stroma, varied in forms : Rounded, Oval, and Irregular in shape, also varied in their sizes: small, medium and large. Saw-scaled viper snake had giant islets prevalent in the region adjacent to the spleen.